Understanding local people's use of time: a pre-condition for good co-management - Colfer, C.J.P.; Wadley, R.L.; Venkateswarlu, P. (1999)
Development of management plans collaboratively with local people (e.g. co-management) is now an important means of protected area conservation. Yet formal protected area managers often need more specific information about the local people with whom they want to co-manage resources. We propose wider use of a method, which we describe, for studying time allocation, as an early step in the co-management of conservation areas. Use of time allocation data in co-management is illustrated from a conservation project in Danau Sentarum Wildlife Reserve (DSWR) in West Kalimantan, Indonesia. Data from spot observations were analysed at three levels, namely those of 'macro-categories' (production, reproduction and leisure), an intermediate level (e.g. agriculture and f ood preparation), and that of individual activities (such as fishing, collection of forest foods and hunting). In the DSWR, the allocation of time differed according to gender, ethnicity and seasonality, throughout the year of the study. Our experience suggests that knowledge of such patterns of behaviour can help conservation area managers to understand local people's needs and desires better, improve managers' rapport with local people, and make better cooperative plans with local people